Manger la parole de Dieu. La Bible lue par les Wari’ - Aparecida Vilaça (Journal de la Société des Américanistes)
Eating God’s Words: the Bible as read by the Wari’. This paper deals with one particular aspect of Christianity as experienced by the Wari’ (Amazonia, Brazil): the interest they take in the Bible, which has been translated into their language by the New Tribes missionaries who have been living among them for nearly fifty years now. The comparison of God’s Words with food equates reading or hearing them with other native ways of producing kinship. This process is reinforced by the moral contents of the Holy Words, as well as by their ontological premises, since the clear-cut distinction between human and non-human animals helps to ratify the Wari’s human status.